Modified hydroponics and phenolic foam as technological innovations in the production of coffee seedlings from cuttings - Cunha, Samuel Henrique; Lima, Amador Eduardo; Carvalho, Alex Mendonça [UNESP]; Guimarães, Rubens José; Castro, Elisa Melo; Faria, Mauro Magalhães; Teramoto, Erico Tadao [UNESP] (Universidade Estadual de Londrina, 2022)
Brazilian coffee production represents an important activity in the country's agricultural sector and, for this reason, it requires innovative technologies for the production of seedlings, which is one of the most important inputs in crop implantation. Thus, plant cloning by cutting, mineral nutrition via modified hydroponics and the use of alternative substrates appear as technological innovations for seedling production. This study evaluated the production of clonal coffee seedlings in a modified hydroponic system in comparison to the conventional climate-controlled greenhouse system, using vermiculite and phenolic foam as alternative substrates. At the end of the experiment, the seedlings were analyzed for growth (height, stem diameter, number of total leaves, leaf area, root area, shoot and root dry matter) and physiological (chlorophyll content and stomatal conductance) characteristics. For the statistical analysis, a completely randomized design was used in a factorial scheme 2 (types of substrate) x 2 (cultivation systems) with six replications and ten plants per plot. The innovative modified hydroponic system leads to a greater growth of coffee seedlings produced by cuttings in tubes with vermiculite compared to those produced in conventional systems. The substrate phenolic foam can be used alternatively in the air-conditioned greenhouse system. However, in the modified hydroponic system, it is not indicated, as it causes total seedling mortality.
Hidroponia modificada e espuma fenólica como inovações tecnológicas na produção de mudas de cafeeiro oriundas de estacas
Keywords: Citrus sinensis; Conservation agriculture; Glyphosate; Urochloa